The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1101/2023.01.05.23284220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct Economic Burden of Mental Health Disorders Associated with Polycystic Ovary Syndrome: Systematic Review and Meta-analysis

Abstract: BACKGROUND: Polycystic ovary syndrome (PCOS) is the most common hormone disorder affecting about one in seven reproductive-aged women worldwide and approximately 6 million women in the United States (U.S.). PCOS can be a significant burden to those affected and is associated with an increased prevalence of mental health (MH) disorders such as depression, anxiety, eating disorders, and postpartum depression. We undertook this study to determine the excess economic burden associated with MH disorders in women wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…137 The healthcare costs associated with anxiety, depression, and eating disorders in the US were estimated to be $4.26 billion per year in 2021. 29 Our data show that dementia-related symptomology coded in the administrative database was increased 2-fold in those with PCOS and that it occurs 19 years earlier in those with PCOS, compared to the age in controls. This finding requires further investigation into the symptoms vs the early onset of cognitive decline specific to dementia or Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…137 The healthcare costs associated with anxiety, depression, and eating disorders in the US were estimated to be $4.26 billion per year in 2021. 29 Our data show that dementia-related symptomology coded in the administrative database was increased 2-fold in those with PCOS and that it occurs 19 years earlier in those with PCOS, compared to the age in controls. This finding requires further investigation into the symptoms vs the early onset of cognitive decline specific to dementia or Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 53%
“…This prevalence of eating disorders is relatively high compared to that found in other population studies that report a 0.3%-2.45% prevalence in those with PCOS. 31 , 126 , 129 , 130 However, in meta-analyses, a prevalence ratio of 1.2 and an odds ratio of 3.8 have been reported for eating disorders in those with PCOS, compared to controls, 29 , 131 and in case control studies, the prevalence of an eating disorder has been reported to range from 11% to 62%. 132 , 133 , 134 , 135 , 136 We have reported that the eating disorders seen in those with PCOS are most commonly bulimia nervosa and binge eating disorder.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations